<<

ECE 307

Fourier Transform

Z. Aliyazicioglu Electrical & Computer Engineering Dept. Cal Poly Pomona

Fourier Transform

The Fourier transform (FT) is the extension of the Fourier to nonperiodic signals. The Fourier transform of a signal exist if satisfies the following condition.

∞ 2 ∫ xt() dt< ∞ −∞

∞ The Fourier transform X()ω = ∫ xte ()− jtω dt −∞

The inverse Fourier transform (IFT) of X(ω) is x(t)and given by

1 ∞ x()tXed= ∫ (ω ) jtω ω 2π −∞

1 Fourier Transform

Also, The Fourier transform can be defined in terms of of as

∞ X()fxtedt= ∫ () − jft2π −∞

and corresponding inverse Fourier transform is

∞ x()tXfedf= ∫ () jft2π −∞

Fourier Transform

Example: Determine the Fourier transform of a rectangular pulse shown in the following figure x(t)

h a /2 ωωaa − jj − jtω h   Xhedtee()ω ==− 22 ∫ − jω t −a /2   ωa -a/2 a/2 sin( ) 2haω ==sin( ) ha 2 ω 2 ωa 2 ωa = hasinc  2π

2 Fourier Transform

Example: To find in ,

a /2 22ππfa fa − jj − jft2π h   Xf()==∫ he dt e22 − e  −a /2 − jf2π   h = 1, hfasin(π ) ==sin(πfa ) ha a = 1 ππffa ω = hasinc fa X()ω = 2sinc () 2π

>> h=1; >> a=1; >> f=-3.5:0.01:3.5; >> w=2**f; >> x=h*a*sinc(w*a/(2*pi)); >> plot (w,x) >> title ('X(\)') >> xlabel('\omega'); >>

Fourier Transform

h = 1, a = 2 ω2 X()ω = 2sinc 2π

>> h=1; >> a=1; >> f=-3.5:0.01:3.5; >> w=2*pi*f; >> x=abs(h*a*sinc(w*a/(2*pi))); >> subplot (2,1,1) >> plot (w,x) >> title ('|X(\omega)|') >> xlabel('\omega') >> xp=(h*a*sinc(w*a/(2*pi))); >> subplot (2,1,2) >> plot (w,xp) >> title ('phase X(\omega)') >> xlabel('\omega')

3 Fourier Transform

Example

Determine the Fourier transform of the δ(t)

∞ Xtedte()ωδ===∫ ()−−jtωω j0 1 −∞

X(ω) 1

ω

Fourier Transform

Properties of the Fourier Transform We summarize several important properties of the Fourier Transform as follows.

1. Linearity (Superposition)

xt()⇔ X (ω ) If xt11()⇔ X (ω ) and 22

Then, ax11() t+⇔+ ax 2 2 () t aX 1 1 (ω ) aX 2 2 (ω )

Proof: ∞∞∞ axt()+= axte ()−−jtωω dta xte () jt dta + xte () − jt ω dt ∫∫∫[]11 2 2 1 1 2 2 −∞ −∞ −∞

=+aX11()ωω aX 2 2 ()

4 Fourier Transform

Properties of the Fourier Transform

2. Time Shifting

If xt()⇔ X (ω )

− jωt0 Then, xt()−⇔ t0 X ()ω e

Proof: Let τ =−tt0 then tt= τ + 0 and dt= dτ

∞∞ jt() xt()−= t e− jtω dt x ()τ e−+ωτ 0 dτ ∫∫0 −∞ −∞ ∞ jt = exed− ω 0 ∫ ()τ − jωτ τ −∞ jt = eX− ω 0 ()ω

Fourier Transform

Let yt()=− xt ( t0 )

j tjt YXeXee()ωω== ()−−ω 00 () ωjX∠ ()ω ω

= Xe()ω jX(())∠−ωω t0

Ye()ωωjY∠ ()ω = Xe () j(())∠−Xtωω0

Therefore, the spectrum of the time shifted signal is the same as the amplitude spectrum of the original signal, and the phase spectrum of the time-shifted signal is the sum of the phase spectrum of the original signal and a linear phase term.

5 Fourier Transform

Example: Determine the Fourier transform of the following time shifted rectangular pulse.

x(t) h a ωa − jω Xhae()ω = sinc 2 2π t

0 a >> h=1; >> a=1; >> f=-3.5:0.01:3.5; >> w=2*pi*f; >> x=abs(h*a*sinc(w*a/(2*pi)).*exp(- j*w*1/2)); >> subplot (2,1,1) >> plot (w,x) >> title ('|X(\omega)|') >> xlabel('\omega') >> xp=phase(h*a*sinc(w*a/(2*pi)).*exp(- j*w.*1/2)); >> subplot (2,1,2) >> plot (w,xp) >> xlabel('\omega') >> title ('phaseX(\omega)')

Fourier Transform

3. Time Scaling

If xt()⇔ X (ω ) then 1 ω xat()⇔ X () aa

Proof: Let τ = at then ta= τ / and dt= (1/ a ) dτ

If , a>0 then If , a<0 then

∞∞ω − j τ ∞∞ω − jtω 1 − j τ 1 x()at e dt= x ()τ ea dτ xate()− jtω dt= x ()ττ ea d ∫∫ ∫∫a −∞ −∞ a −∞ −∞ ∞ ω 1 ω 11− j τ ω = X() ==∫ xe()ττa d X ( ) aa aaa−∞

6 Fourier Transform

Example. if , xt () ⇔ X ( ω ) then find the Fourier transform of the following signals 1 −ω xt(2)−⇔ X ( ) a. 22 b. xt(/5)⇔ 5 X (5)ω 1 −ω c. xt(5(−− 2)) ⇔ X ( ) e− jω 2 55

Example: Find the Fourier transform of the following signal.

ω xt11()=∏ () t ⇔ X (ω ) = sinc a. 2π 11ω ω xt() (5) t X ( ) X ( ) sinc b. 221=∏ ⇔ω = =  555 10π c. ω xt331()=∏ ( t /5) ⇔ X (ωω ) = 5 X (5) = 5sinc 0.4π

Fourier Transform

4. (Symmetry) If xt()⇔ X (ω ) then

Xt()⇔− 2π x (ω ) or X()txf⇔ (− )

Proof: Since t and ω are arbitrary variables in the inverse Fourier transform

1 ∞ x()tXed= ∫ (ω ) jtω ω 2π −∞ we can replace ω with t and t with - ω to get

∞ 1 − jtω Therefore, xXtedt()−=ω ∫ () 2π −∞ ∞ F{}Xt()==−∫ Xte ()− jtω dt 2π x (ω ) −∞

7 Fourier Transform

Similarly, if we can replace f with t and t with -f in the inverse Fourier transform

∞ x()tXfedf= ∫ () jft2π −∞

to get ∞ x()−=fXtedf∫ ()− jft2π −∞ Therefore, F{Xt()} = x (− f )

Fourier Transform

Example: xt()=⇔δ () t X (ω ) = 1 Applying symmetry property,

xt()=⇔ 1 X (ω ) = 2πδ ( −= ω ) 2 πδ ( ω ) (δ () ω is even function)

or xt()=⇔ 1 Xf () =−=δ ( f )δ () f

Example: ta ω  xt()=⇔= rect X (ω ) a sinc   a 2π  ta −ω ω xt()=⇔== a sinc X (ωπ ) 2 rect  2 π rect  2π aa 

a Let c = then ac= 2π 2π ωω1  x() t=⇔== a sinc() ct X (ωπ ) 2 rect rect  22πcc π c

8 Fourier Transform

Time Reversal If xt()⇔ X (ω ) then

xt()−⇔− X (ω )

Proof: Let −=t τ . Then t = −τ and dt= − dτ

∞∞ ∫∫xtedt()−=−=−−−−jtωωτ x ()τ e j() dτω X ( ) −∞ −∞

Fourier Transform

Frequency Shifting If xt()⇔ X (ω ) then

− jtωc xte()⇔− X (ω ωc )

Proof:

∞∞ xte()jtωωωcc e− jtω dt==− xte ()−− j() t dt X (ω ω ) ∫∫ c −∞ −∞

9 Fourier Transform

Example: Determine the Fourier transform of cos ω c t and sinωct

11 xt()==+ cosω t ejtωωcc e− jt ⇔=−++ X (ωπδωωδωω )[] ( ) ( ) ccc22

or 11 1 x()tteeXfffff==+ cosωδδjtωωcc− jt ⇔=−++ ()[] ( ) ( ) ccc22 2 X(f) 1/2

-fc fc f The phase spectrum is zero everywhere.

Fourier Transform

11jtωωcc− jt xt()== sinωc t e − e ⇔=−−−+ X (ωπδωωδωω ) j [] (cc ) ( ) 22jj 11 − j x()ttee== sinωδδjtωωcc −− jt ⇔= Xfffff ()[] ( −−+ ) ( ) c 22jj 2cc

|X(f)| 1/2

-fc fc f θ(f) π/2

fc

-fc f -π/2

10 Fourier Transform

7. Modulation If xt()⇔ X (ω ) then 1 xt( )cos(ωccc t )⇔−++[] X (ωω ) X ( ωω ) 2

Proof:

∞∞ 1 jt jt xt()cos(ω te )−−jtωω dt=+ xt ()  eωωcc e e jt dt ∫∫c  −∞ −∞ 2 ∞∞ 1  −−jt()ωω −+ jt () ωω  =+ xte()cc dt xte () dt 2 ∫∫ −∞ −∞  1 =−++[]XX()()ωωcc ωω 2

Fourier Transform

8. Time Differentiation: If xt()⇔ X (ω ) then General case

n dx() t dxt() n ⇔ jXω ()ω n ⇔ ()()jXω ω dt dt

Proof: Taking the of the inverse Fourier transform

1 ∞ x()tXed= ∫ (ω ) jtω ω 2π −∞ we obtain dx() t 1 ∞ = ∫ jωXed()ωωjtω dt 2π −∞

Therefore dx() t ⇔ jXω ()ω dt

11 Fourier Transform

9. Time Differentiation: If xt()⇔ X (ω ) then General case

dXn ()ω dX() jω txtnn()⇔ j tx() t⇔ j dω n dω Proof: Taking derivative of Fourier Transform

∞ − jtω X()ω = ∫ xte () dt with respect to ω, we obtain −∞

dX()ω ∞ =−∫ ()()jtxte− jtω dt dω −∞ dX() jω Therefore tx() t⇔ j dω

Fourier Transform

10 Conjugate If xt()⇔ X (ω ) then

xt**()⇔− X (ω )

Proof: * ∞∞ *()*−−−jtωω j t ∫∫xte() dt=  xte () dt=− X (ω ) −∞ −∞

If x(t) is real x * () txt = () so that XX()ω = * (−ω )

12 Fourier Transform

11.

If xt()⇔ X (ω ) , ht () ⇔ H ( ω ) , and yt () ⇔ Y (ω ) ∞ yt()==− ht ()* xt ()∫ h (τ ) xt (ττ ) d −∞ YHX()ω = ()()ωω Proof:

∞∞ − jtω Yhxtdedt()ωτττ=−∫∫ ()( ) −∞ −∞ Interchanging the order of integration, we obtain

∞∞ ∞∞  −−jjωτ ωτ Yhxtedtd()ω =− ()τττ ( )− jtω YhXedXhed()ω ==∫∫ ()()τω τ () ω () τ τ ∫∫−∞ −∞ −∞ −∞ = XH()()ωω

Fourier Transform

12.

xt()⇔ X (ω ) If 11 , and xt 22 () ⇔ X (ω )

11∞ x ()tx () t⇔=− X (ωω )* X ( ) X ( vX ) ( ω vdv ) 12 1 2∫ 1 2 22ππ−∞

or

∞ x ()tx () t⇔=− X ()* f X () f X ( vX ) ( f vdv ) 12 1 2∫ 1 2 −∞

13 Fourier Transform

13. Parseval’s Theorem

If xt11()⇔ X (ω ) , then total normalized(based on one ohms resistor) E of and x(t) is given by

∞∞∞ 2221 ExtdtXd==∫∫∫() (ωω ) = Xfdf () −∞2π −∞ −∞ Proof

∞∞ ∞∞ 2 ** 1 − jtω  x()tdtxtxtdtxtXeddt== () () () (ωω )  ∫∫ ∫∫2 −∞ −∞ −∞ π −∞ 

Interchanging the order of integration, we obtain

Fourier Transform

Proof (cont)

∞∞∞ 2 1 * − jtω x()tdt= X (ω ) xtedtd () ω ∫∫∫2 −∞π −∞ −∞ 1 ∞ = ∫ XXd* ()()ωωω 2π −∞ ∞ 1 2 = ∫ Xd()ωω 2π −∞

14